Research on Cost Control Optimization of Yango Group Real Estate Company - Bao, Yihan (Transactions on Economics, Business and Management Research, 2026)
Against the background of increasingly fierce competition and stricter government regulation in the real estate industry, cost control has become critical to the survival and development of real estate enterprises. Taking Yango Real Estate Company as the research object, this paper analyzes its current cost control status, organizational structure, institutional system and cost composition data, and identifies prominent problems such as outdated management concepts, insufficient awareness of full-staff cost control, ineffective control of labor costs, overspending of marketing expenses, poor management of material costs and delayed feedback of dynamic costs. The root causes lie in insufficient authorization of cost control departments, imperfect responsibility–power–benefit system, lack of collaborative culture and inadequate accumulation of cost data. Based on relevant theories of cost control, this paper puts forward targeted optimization strategies, including establishing full-staff and all-round cost control awareness, rationally allocating and controlling labor costs, strengthening marketing and material cost control, and feeding back and adjusting dynamic costs in a timely manner. The conclusions of this study can help Yango Real Estate improve its management level, reduce costs and increase efficiency, and also provide reference for cost control practices of other real estate enterprises.
Keywords: real estate enterprise; cost control; cost optimization.